Rapid Detection of Contagious Caprine Pleuropneumonia Using a Mycoplasma capricolum subsp. capripneumoniae Capsular Polysaccharide-Specific Antigen Detection Latex Agglutination Test - March, J. B. (American Society for Microbiology, 2000)
Latex microspheres (diameter, 8 μm) were coated with anti-Mycoplasma capricolum subsp. capripneumoniae polyclonal immunoglobulin G (IgG) antiserum (anti-F38 biotype). The coated microspheres, when used in a latex agglutination test (LAT), detected M. capricolum subsp. capripneumoniae antigen in the serum of goats with contagious caprine pleuropneumoniae (CCPP). Beads also agglutinated strongly in the presence of purified M. capricolum subsp. capripneumoniae capsular polysaccharide (CPS). Preabsorption of CPS-specific antibodies prior to coating of the beads removed agglutinating activity in the presence of M. capricolum subsp. capripneumoniae, strongly suggesting that CPS is the likely soluble antigen recognized by the test. In addition, the specificity of the LAT exactly mirrored that of an M. capricolum subsp. capripneumoniae CPS-specific monoclonal antibody (WM25): of the 8 other mycoplasma species tested, agglutination was observed only with bovine serogroup 7. The LAT detected all 11 strains of M. capricolum subsp. capripneumoniae examined in this study, with a sensitivity level of 2 ng of CPS, or the equivalent of 1.7 × 10(4) CFU, in a reaction volume of 0.03 ml of serum. With field sera from goats with CCPP, the results of the LAT exhibited a 67% correlation with the results of the currently used complement fixation test (CFT), with the main discrepancy in diagnosis resulting from the increased sensitivity of the LAT compared to that of CFT. This antigen-detection LAT should prove particularly useful in identifying animals in the earliest stages of CCPP and combines sensitivity and low cost with ease of application in the field, without the need for any specialist training or equipment.